Freight Transport, Seamlessness, and Competitive Advantage in the Global Economy - Capineri, Cristina; Leinbach, Thomas R. (European Journal of Transport and Infrastructure Research, 2006)
Freight transport has emerged as one of the most critical and dynamic aspects of the transport sector where change has become the norm. It is now the main element supporting global commodity and more generally supply chains. Yet the lack of seamlessness and inefficiencies in general as well as the rising costs and complexities of shipping and delivering goods are adding to profit pressures faced by manufacturers across the globe. Our paper first discusses the concept of seamlessness, and then examines some of the consequences of the lack of seamlessness in terms of freight transport inefficiencies. We then begin to examine the new developments in which intermodality, technology (e-commerce), and logistics are changing and will have the impact of heightening competitive advantage and reducing constraint points in production value chains and global production networks. Finally the intent is to show how research on this theme might be advanced in a trans-Atlantic framework.